CA1 Spike Timing is Impaired in the 129S Inbred Strain During Cognitive Tasks. (21st February 2022) - Adeyelu, Tolulope; Shrestha, Amita; Adeniyi, Philip A.; Lee, Charles C.; Ogundele, Olalekan M.
Highlights: The firing rate of putative CA1 neurons was assessed in freely behaving inbred mice. 129S CA1 pyr and int units have lower firing rate scores than B6 neurons. 129S CA1 putative int show significant FR variability. The detectability index for putative pyr/int pairs is significantly lower in 129S CA1. Abstract: A spontaneous mutation of the disrupted in schizophrenia 1 ( Disc1 ) gene is carried by the 129S inbred mouse strain. Truncated DISC1 protein in 129S mouse synapses impairs the scaffolding of excitatory postsynaptic receptors and leads to progressive spine dysgenesis. In contrast, C57BL/6 inbred mice carry the wild-type Disc1 gene and exhibit more typical cognitive performance in spatial exploration and executive behavioral tests. Because of the innate Disc1 mutation, adult 129S inbred mice exhibit the behavioral phenotypes of outbred B6 Disc1 knockdown ( Disc1 −/− ) or Disc1-L-100P mutant strains. Recent studies in Disc1 −/− and L-100P mice have shown that impaired excitation-driven interneuron activity and low hippocampal theta power underlie the behavioral phenotypes that resemble human depression and schizophrenia. The current study compared the firing rate and connectivity profile of putative neurons in the CA1 of freely behaving inbred 129S and B6 mice, which have mutant and wild-type Disc1 genes, respectively. In cognitive behavioral tests, 129S mice had lower exploration scores than B6 mice. Furthermore, the mean firing rate for 129S putative pyramidal (pyr) cells and interneurons (int) was significantly lower than that for B6 CA1 neurons sampled during similar tasks. Analysis of pyr/int connectivity revealed a significant delay in synaptic transmission for 129S putative pairs. Sampled 129S pyr/int pairs also had lower detectability index scores than B6 putative pairs. Therefore, the spontaneous Disc1 mutation in the 129S strain attenuates the firing of putative pyr CA1 neurons and impairs spike timing fidelity during cognitive tasks.